Impacto de um método de polimento adicional em propriedades físicas, micromorfológicas e microtopográficas de compósitos convencionais e Bulk Fill - Borges, Giovanna de Fátima Alves da Costa (2018)
The objective of this study was to evaluate the surface roughness, wettability, the depth distribution of the charge particles, the mapping of chemical elements, the 3D microtopography and the micromorphology of the composites of the conventional and bulk fill after additional polishing. The specimens were prepared from each of the composites tested, four of them being bulk fillers (Filtek Bulk Fill Tetric N-Ceram Bulk Fill Opus Bulk Fill X-tra Fil) and four conventional ones (Filtek Z250 XT, Grandioso, Tetric N-Ceram, Vittra APS ), according to three additional finishing / polishing / polishing techniques (n = 10): without finishing and polishing, finishing and polishing with abrasive rubbers (Astropol), finishing and polishing with Astropol plus additional polishing with silicon carbide brush. The surface roughness (Ra) and contact angles were measured using a profilometer and adapted goniometer, respectively. The 3D microtopography was evaluated using atomic force microscopy (AFM); while the micromorphology and the in-depth arrangement of the charge particles by scanning electron microscopy (SEM).The mapping of chemical elements was evaluated by means of X-ray Dispersive Energy Spectroscopy (EDS). The roughness and the contact angle were analyzed by ANOVA-twofactors and Tukey test (p <0.05); the other data were analyzed descriptively. The arrangement of the in-depth charge particles of all the resins involved in this study had an organic matrix rich surface layer and a particulate rich subsurface layer of smaller dimensions.Addicionalpolishing: reduced surface roughness of Filtek Bulk Fill resins, Vittra APS, Tetric N-ceram Bulk Fill and X-trafil resins; increased the contact angle value of the X-tra Fil and decreased the Filtek Z250 XT. In the analyzes for 3D microtopography and micromorphology, smoother and more uniform surfaces were observed in all a resins. The elements: carbon (C), oxygen (O), silicon (Si), zirconia (Zr) and aluminum (Al) were present in all composite resins. Barium (Ba) was absent on Filtek Z250 XT, Filtek Bulk Fil and Vittra APS. Carbon was predominant in all resins. Afteradditional polishing, there was an increase in oxygen detection for all resins except for Tetric N-Ceram and X-tra Fil and a decrease in carbon except for Tetric N-Ceram Bulk Fil. Silicon decreased only in the Z250 XT, Tetric N-Ceram and Tetric N-Ceram Bulk Fill resins. Zirconia decreased for Tetric N-Ceram Bulk Fill and aluminum for Z250 XT and Tetric N-Ceram Bulk Fill. Barium increased for Opus Bulk fill and X-tra Fil. Titanium was absent for all resins. Therefore, additional polishing improved the surface properties of the resins studied.